Answer:
A. 4x⁴ - 4x³ - 16x² - 16x
B. 4x⁴ - 4x³ - 16x² + 16x
Explanation:
If you want to find the product of 2 binomial (or even polynomial) expressions, you simply need to multiply every term in one expression by every term in the other:
A.
(4x² - 4x)(x² - 4) = 4x²(x²) + 4x²(-4) - 4x(x²) - 4x(4)
= 4x⁴ - 16x² - 4x³ - 16x
= 4x⁴ - 4x³ - 16x² - 16x
B.
(x² + x - 2)(4x² - 8x) = x²(4x²) + x(4x²) - 2(4x²) + x²(-8x) + x(-8x) - 2(-8x)
= 4x⁴ + 4x³ - 8x² - 8x³ - 8x² + 16x
= 4x⁴ - 4x³ - 16x² + 16x
Descending order simply means the powers must be largest first and smallest last.